Short-Chain Fatty Acid Butyrate Induces Cilia Formation and Potentiates the Effects of HDAC6 Inhibitors in Cholangiocarcinoma Cells - Pant, Kishor; Richard, Seth; Gradilone, Sergio A. (Frontiers in Cell and Developmental Biology, 2022)
Cholangiocarcinoma (CCA), is a deadly form of liver cancer with limited therapeutic approaches. The pathogenesis of CCA involves the loss of primary cilia in cholangiocytes, an important organelle that regulates several key cellular functions including the regulation of cell polarity, growth, and differentiation, by a mechanism involving increased expression of deacetylases like HDAC6 and SIRT1. Therefore, cilia restoration may represent an alternative and novel therapeutic approach against CCA. Butyrate is a produced by bacterial fermentation of fibers in the intestine and has been shown to inhibit SIRT1, showing antitumor effects on various cancers. Herein, we investigated the role of butyrate on CCA cells proliferation, migration, EMT and evaluated the synergistic effects with specific HDAC6 inhibition. When CCA cells, including HuCCT1 and KMCH, were treated with butyrate, the cilia formation and acetylated-tubulin levels were increased, while no significant effects were observed in normal human cholangiocytes. Butyrate treatment also depicted reduced cell proliferation in HuCCT1 and KMCH cells but, on the other hand, it affected cell growth of the normal cholangiocytes only at high concentrations. In HuCCT1 cells, spheroid formation and cell migration were also halted by butyrate treatment. Furthermore, we found that butyrate augmented the previously described effects of HDAC6 inhibitors on CCA cells proliferation and migration by reducing the expression of CD44, cyclin D1, PCNA, Zeb1, and Vimentin. In summary, butyrate targets cancer cell growth and migration, and enhances the anti-cancer effects of HDAC6 inhibitors in CCA cells, suggesting that butyrate may have therapeutic effects in CCA and other ciliopathies.